Deciphering the mechanism for the assembly of aromatic polyketides by a bacterial polyketide synthase. - Shen, B (1996)
Aromatic polyketides are assembled by a type 11 (iterative) polyketide synthase (PKS) in bacteria. Understanding the enzymology of such enzymes should provide the information needed for the synthesis of novel polyketides through the genetic engineering of PKSs. Using a previously described cell-free system [B.S. & C.R.H. (1993) Science 262, 1535-1540], we studied a PKS enzyme whose substrate is not directly available and purified the TcmN polyketide cyclase from Streptomyces glaucescens. TcmN is a bifunctional protein that catalyzes the regiospecific cyclization of the Tcm PKS-bound linear decaketide to Tcm F2 and the 0-methylation of Tcm D3 to Tcm B3. In the absence of TcmN, the decaketide formed by the minimal PKS consisting of the TcmJKLM proteins undergoes spontaneous cyclization to form some Tcm F2 as well as SEK15 and many other aberrant shunt products. Addition of purified TcmN to a mixture of the other Tcm PKS components both restores and enhances Tcm F2 production. Interestingly, Tcm F2 but none of the aberrant products was bound tightly to the PKS. The results described support the notion that the polyketide cyclase, not the minimal PKS, dictates the regiospecificity for the cyclization of the linear polyketide intermediate. Furthermore, because the addition of TcmN to the TcmJKLM proteins results in a significant increase of the total yield of decaketide, interactions among the individual components of the Tcm PKS complex must give rise to the optimal PKS activity.